Real-time power system impedance estimation for DG applications: Using PV-inverter based harmonic injection method - Knezevic, Aleksa (Department of Electrical Engineering, 2017)
On-line power system (PS) Thévenin equivalent impedance (TEI) estimation involves the reduction of the PS's complex circuit into a simple form that provides valuable insight into its state and behaviour. It finds application in numerous areas such as voltage stability monitoring and islanding detection. In the context of distributed generation (DG), on-line TEI estimation can be easily implemented in existing hardware to add functionality and improve the operation of power converters – the key components of DG systems. Two distinct methods of on-line PS TEI estimation exist. The passive method involves only measurement of voltage and current, whereas the active method involves injection of current into the PS and measurement of the response. This work is focused on the active method. Through a review of the available literature, limitations of past work are highlighted. It is shown that the nature of current injection varies greatly in different works and that evaluation of implementation performance is generally not thorough. Little consideration has been made of the effect of injection current level and frequency on the performance of on-line TEI estimation. Furthermore, the behaviour of the grid and its impact has not been thoroughly investigated. In this work, the active method is implemented in a three-phase PV-inverter and thoroughly tested in terms of its TEI estimation accuracy. Dependence of said accuracy on parameters such as the level of injected current and its frequency is shown to be high through tests performed on the live PS at two locations. These parameters are optimised such that TEI accuracy is maximised and the performance of the device is shown to be good compared to calibration equipment. The accuracy of PS TEI tracking is evaluated and quantified. Considerations are also made of the device's hardware limitations and their effect. A process by which a device's TEI estimation accuracy can be thoroughly evaluated is developed through this work. The behaviour of the PS's TEI is also investigated over long periods and characterised. It is found that the TEI remains steady around an average level in both test locations, with a low standard deviation. Consistency in results is found to be high between the two tests.